AN ECOCRITICAL DISCOURSE ANALYSIS OF ANTHROPOCENTRISM IN THE CAMEROONIAN PRESS - Walter Abo Acha (International Journal of Humanity Studies (IJHS), 2022)
The manner in which the media presents nature matters a lot. The media legitimises abusive beliefs. On this basis, this work investigated the ecologically oppressive ideologies reinforced by the Cameroonian English newspaper. Analysis focused on uncovering-to-resist discursive patterns that activated anthropocentrism (human dominance over nature). The data comprised thirty-five newspaper articles randomly selected from nine English Language newspaper publishers in Cameroon. Ecocriticrical discourse analysis (EcoCDA) is the theoretical framework adopted in this study. The descriptive statistical method (DSM) was used to analyse the data. Analyses subsumed identification, quantification and interpretation of discourse entities. Findings revealed that the Cameroonian press used diverse language patterns to manipulate agents, processes and aftermaths of environmental depletion. The press, thus, encoded anthropocentric ideologies in discursive forms like pronouns, verbs, transitivity, personification and jargon. Ecological injustices uncovered and resisted included deforestation, consumerism and growth, mineral extraction and construction, inter alia. Cognizant of the sustenance nature that offers earthly life, it was recommended that press [wo]men should refrain from manipulative language forms and stories that downplay efforts to conserve nature. They should rather cover nature-conserving stories regularly, and in language forms that align with and reinforce global efforts to protect and conserve the biophysical environment.